2021
DOI: 10.3389/fcell.2021.657623
|View full text |Cite
|
Sign up to set email alerts
|

1800 MHz Radiofrequency Electromagnetic Field Impairs Neurite Outgrowth Through Inhibiting EPHA5 Signaling

Abstract: The increasing intensity of environmental radiofrequency electromagnetic fields (RF-EMF) has increased public concern about its health effects. Of particular concern are the influences of RF-EMF exposure on the development of the brain. The mechanisms of how RF-EMF acts on the developing brain are not fully understood. Here, based on high-throughput RNA sequencing techniques, we revealed that transcripts related to neurite development were significantly influenced by 1800 MHz RF-EMF exposure during neuronal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 78 publications
0
8
1
Order By: Relevance
“…The activity and density of mature spines in primary hippocampal neurons decrease significantly when exposed to 2.4 W/kg RF-EMR, and the average length of dendrites per neuron is also reduced ( 14 ). We also showed that RF-EMR exposure impairs neurite outgrowth in neural stem cell-derived neurons ( 15 , 16 ). However, a study using a pulsed radiofrequency electromagnetic field reported that it can potentiate neurite outgrowth in the dopaminergic MN9D cell line ( 17 ).…”
Section: Introductionmentioning
confidence: 65%
See 2 more Smart Citations
“…The activity and density of mature spines in primary hippocampal neurons decrease significantly when exposed to 2.4 W/kg RF-EMR, and the average length of dendrites per neuron is also reduced ( 14 ). We also showed that RF-EMR exposure impairs neurite outgrowth in neural stem cell-derived neurons ( 15 , 16 ). However, a study using a pulsed radiofrequency electromagnetic field reported that it can potentiate neurite outgrowth in the dopaminergic MN9D cell line ( 17 ).…”
Section: Introductionmentioning
confidence: 65%
“…Kim et al reported that the total number of dendritic spines was significantly decreased in hippocampal neurons after RF-EMR exposure at 4 W/kg for 4 weeks ( 9 ). Our previous studies also showed that 72 h of 1,800 MHz RF-EMR exposure significantly inhibited neurite outgrowth in embryonic neural stem cells (eNSCs) at 4 W/kg, in which the BHLH gene and the EPHA5 signaling pathway were involved ( 15 , 16 ). The mechanisms underlying the effects of RF-EMR exposure on neurite outgrowth or synaptic plasticity are thought to include changes in calcium ion channels, the myelin sheath, oxidative stress and the glutamate receptor signaling pathway ( 36 , 41 , 42 ).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The biological effects of exposure to EMFs have been investigated in several studies, particularly in experimental mouse studies 10 . However, the biological effects of such exposure on the development of the brain and the underlying mechanisms have still not been completely elucidated 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The usage of wireless communication devices has become a ubiquitous part of daily personal and professional life 1 , resulting in an augmented public exposure to radiofrequency electromagnetic radiation (RF-EMF) 2 . Long-term exposure to RF-EMF emitted by various electronic devices has been propounded to result in hazardous biological and health effects 3 .…”
Section: Introductionmentioning
confidence: 99%